2009
DOI: 10.1271/bbb.90130
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Effect of a Hot-Water Extract of Quince (Cydonia oblonga)

Abstract: We examined the effect of a crude hot-water extract (HW) of quince (Cydonia oblonga Miller) fruit on type I allergy in vivo and in vitro. The oral administration of the quince HW-added diet to NC/Nga mice for 63 d showed a significant decrease in the development of atopic dermatitis-like skin lesions under conventional conditions. The concentration of IgE in the serum collected from mice fed with quince HW was also lowered in a dose-dependent manner. Moreover, we found that quince HW inhibited the release of -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 41 publications
2
30
0
1
Order By: Relevance
“…Quince HW was prepared as described previously (Shinomiya et al 2009). In brief, the peel, pulp and seeds of quince fruits were cut into pieces, and then boiled in hot water for 1 h. After filtering the extract through a layer of cloth, the filtrate was centrifuged at 5,0009g for 30 min.…”
Section: Preparation Of Quince Hwmentioning
confidence: 99%
See 1 more Smart Citation
“…Quince HW was prepared as described previously (Shinomiya et al 2009). In brief, the peel, pulp and seeds of quince fruits were cut into pieces, and then boiled in hot water for 1 h. After filtering the extract through a layer of cloth, the filtrate was centrifuged at 5,0009g for 30 min.…”
Section: Preparation Of Quince Hwmentioning
confidence: 99%
“…Recently, we reported the anti-allergic effect of a crude hot-water extract (HW) of quince on immediate allergic model NC/Nga mice (Shinomiya et al 2009). Quince HW notably alleviated the severity of atopic dermatitis-like skin lesions with degranulation of serum IgE.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stimulatory activity toward bifidobacterial release assay was employed to evaluate IgE-mediated degranulation in this study (Kobayashi and Tanabe, 2006;Shinomiya et al, 2009). RBL-2H3 cells (2 × 10 5 cells/well)…”
Section: Resultsmentioning
confidence: 99%
“…PG102, an aqueous extract from Actinidia arguta (26), is an example exhibiting such an activity. White rose fetal extract of Rosa rugosa root (27), procyanidin C1 from apple (28), and hot water extract of Cydonia oblonga (29) have shown potential in inhibiting chemical-induced animal model or NC/Nga mice. In the course of screening of anti-atopic agents, we found that an aqueous TcRSE exhibits in vitro antioxidant and free radical-scavenging capability, and has potent T-bet promoter enhancing activity.…”
Section: Discussionmentioning
confidence: 99%